Determination of Customer Order Decoupling Point (CODP) Based on Mass Customization Concept to Minimize Manufacturing Lead Time - Yuli Dwi Astanti; Sadi Sadi; Deni Widiyanto; Puryani Puryani; Trismi Ristyowati (OPSI, 2023)
Make To Order (MTO) is a manufacturing strategy that executes different orders based on consumer demand. In the MTO strategy, products are produced only when there are orders from consumers. In this MTO system, the production process starts when an order arrives and starts with planning raw materials which takes a long time and causes a long lead time (MLT). Long MLT often causes production delays and forces companies to pay more overtime. Companies must adopt a production system that can fulfill a variety of orders and has a fast response time. In this research, a case study was conducted on a shoe and bag manufacturing company in the fashion industry. This study aims to implement a mass customization manufacturing (MC) strategy to minimize MLT. The MC strategy uses the concept of a production process based on orders and inventory. This study is expected to reduce MLT so that production delays do not occur again. The results of this study indicate that relocation of the customer order decoupling point (CODP) can reduce MLT from 30 days to 26 days. By reducing this, production delays can be overcome. In terms of costs, this production system is lower than before and the profits are higher.